Alterations in Somatostatin mRNA Expression in the Dorsolateral Prefrontal Cortex of Subjects with Schizophrenia or Schizoaffective Disorder - Morris, Harvey M. (2008)
Alterations in the inhibitory circuitry of the dorsolateral prefrontal cortex (DLPFC) in schizophrenia include reduced expression of the messenger RNA (mRNA) for somatostatin (SST), a neuropeptide present in a subpopulation of γ-aminobutyric acid (GABA) neurons. However, neither the cellular substrate nor the causal mechanisms for decreased SST mRNA levels in schizophrenia are known. We used in situ hybridization to quantify the compartmental, laminar, and cellular levels of SST mRNA expression in the DLPFC of 23 pairs of schizophrenia or schizoaffective disorder and control subjects. We also explored potential causal mechanisms by utilizing similar methods to analyze SST mRNA expression in 2 animal models. The expression of SST mRNA was significantly decreased in layers 2–superficial 6 of subjects with schizophrenia, but not in layer 1, deep 6 or the white matter. At the cellular level, both the density of cortical SST mRNA-positive neurons and the expression of SST mRNA per neuron were reduced in the subjects with schizophrenia. These alterations were not due to potential confounds and appeared to be a downstream consequence of impaired neurotrophin signaling through the trkB receptor. These findings support the hypothesis that a marked reduction in SST mRNA expression in a subset of GABA neurons contributes to DLPFC dysfunction in schizophrenia.